Nano shell powder foam stabilizer and preparation method thereof

By crushing the shell into nanoparticles, and burning at high temperatures, the ball grinding is formed to form a loose nano -shell powder. The load surface active agent is used to improve the stability and oil -driven effect of the foam. The problem that affects a lot of influence has achieved efficient and environmentally friendly bubble stabilizers.

CN119371951APending Publication Date: 2025-01-28ZHEJIANG OCEAN UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411491918.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing foam stabilizers have problems such as high cost, great environmental impact, poor dispersion and inability to load surfactants, making it difficult to maintain the stability of the foam and oil dispersion effect under high-temperature formation conditions.

Method used

By crushing the shell into nanoparticles, and burning at high temperature, the ball -grinding is formed to form a loose nano -shell powder. The load surface active agent is used to improve the stability and oil -driven effect of the foam.

Benefits of technology

The efficient preparation of nano -shell powder stabilized foaming agent is achieved, the stability and oil -repellent effect of the foam is improved, the production cost is reduced, and it is conducive to environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005100304830000011
    Figure HDA0005100304830000011
  • Figure HDA0005100304830000012
    Figure HDA0005100304830000012
  • Figure HDA0005100304830000021
    Figure HDA0005100304830000021
Patent Text Reader

Abstract

The invention provides a nano shell powder foam stabilizer and a preparation method thereof. The preparation method comprises the following steps: S1, soaking shells in an HCl solution for 24 hours, taking out the shells, cleaning the shells with distilled water until the shells are neutral, and drying the shells to obtain pretreated shells; s2, crushing the pretreated shells, and sieving with a 150-mesh sieve to obtain coarse shell powder; s3, placing the coarse shell powder in a tubular furnace, introducing nitrogen, isolating oxygen, heating to 900-1000 DEG C, and calcining for 3-4 hours to obtain calcined shell powder; s4, carrying out ball milling on the calcined shell powder for 6-8 hours to obtain nano shell powder; and S5, filling the nano shell powder, a surfactant and deionized water into a lining of a high-pressure reaction kettle, putting the high-pressure reaction kettle into a drying oven, heating to 120 DEG C, preserving heat for 24 hours, taking out the lining after the high-pressure reaction kettle is cooled to room temperature, pouring out the mixed solution from the lining, carrying out suction filtration on the mixed solution, and drying to obtain the nano shell powder foam stabilizer. The prepared nano shell powder foam stabilizer has good foam stabilizing performance, high-value development and utilization of shell powder resources are achieved, and environmental protection is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to a foam stabilizer, and particularly relates to a nano shell powder foam stabilizer and a preparation method thereof. Background Art

[0002] Foam has the characteristics of blocking large objects but not small ones, blocking water but not oil, low friction, low density, low filtration, and little damage to the formation. It is widely used in the fields of petroleum industry such as improving oil and gas recovery, oil and gas field development, drilling, cementing, reservoir protection, and reservoir transformation. However, foam is a thermodynamically unstable system and is prone to aggregation, which affects its performance. Therefore, the foaming ability and half-life of foam are crucial to the application of foam in oilfield development. There are many reasons that affect the stability of foam. For example, if the formation temperature is too high, it will affect the foaming volume and half-life of the foaming agent. If the inorganic salt content in the formation is too high, it will also reduce the half-life of the foam. In order to improve the stability of the foam, surfactants, polymers and other additives can be added to the foaming solution. Adding polymers can increase the viscosity of the liquid film and increase the resistance to gas diffusion to improve the stability of the foam. Adding surfactants can form a dense adsorption layer, which can reduce the effective gas permeability of the interface and increase the surface elasticity, thereby inhibiting the aggregation rate of the foam. However, some polymers and surfactants are easily degraded in the formation environment and are severely retained, which increases the cost of using the agent and limits the action distance of the foam.

[0003] As a new type of foam stabilizer, nanoparticles have special surface effects, interface effects and small size effects. They can be used as foam stabilizers to enhance the stability of foam, thereby improving the oil displacement effect of foam in porous media. Moreover, the adsorption of nanoparticles on the gas-liquid interface is a thermodynamically spontaneous process, which can reduce the energy of the system. In addition, nanoparticles adsorbed at the interface can form a solid structure, thereby effectively inhibiting the aggregation of foam and improving the stability of foam. Currently, the nanoparticles used to stabilize foam are mainly nano-SiO 2 , nano aluminum hydroxide, nano cellulose, nano clay, etc., although these commonly used nano foam stabilizing particles can improve the stability of foam and improve its performance under harsh conditions, they also have some disadvantages and challenges: first of all, the cost issue. These nanoparticles are prone to sedimentation and have poor dispersibility. Moreover, there is no porosity on their surface, so they cannot load surfactants and have no ability to alleviate the adsorption loss of surfactants in the formation. The required chemical reagents and treatment steps may lead to increased costs; secondly, there will be environmental impacts. Although some nanoparticles such as silica are considered to be environmentally friendly materials, the production, use and disposal of nanoparticles may have potential impacts on the environment. Therefore, there is an urgent need to find an environmentally friendly, low-cost, highly dispersible and efficient foam stabilizer that can work synergistically with a foaming agent.

[0004] my country ranks first in the world in terms of shellfish production. Shells are the main byproduct of shellfish processing and are extremely abundant. The piles of shells have caused great pollution to the coastal environment, occupied a large amount of coastal land, and wasted a lot of shell resources. More than 90% of shells are CaCO 3 , and 1%-5% organic matrix, and presents a "brick and mud" structure that cannot be synthesized by humans, in which CaCO 3 Mainly aragonite and calcite, shells are therefore low-cost CaCO 3 Source. Because shells have special structures and excellent properties, people hope to further process them to obtain other more valuable materials or preparations. Among them, shell porous materials show excellent adsorption, dispersion, porosity and non-toxicity. Discarded shells can be crushed into nanoparticles. In previous studies, nano shell powder has been made into various bio-based materials, such as oil adsorbents, photocatalyst carriers and photocatalysts. In order to improve the performance of shell powder, the shells are calcined at high temperature, and the CaCO in the shells is 3 And some trace organic matter will gradually decompose. A large amount of energy will be generated during the decomposition process, making the surface of the shell loose and porous, and some active calcium oxide can be obtained after high-temperature calcination.

[0005] At present, some people have selected mussel shells as raw materials, calcined them at high temperature under anaerobic conditions, ground them into powder, and used them for cleaning and sterilizing fruits and vegetables; some people have used mussel shells as raw materials, calcined them at high temperature under anaerobic conditions, ground them into powder, and used hydrothermal synthesis to load alkyl polyglucosides (APG) and rhamnolipid (RL) on the surface of calcined mussel shells to prepare solid green tableware cleaning materials; some people have carried petroleum hydrocarbon degradation bacteria on the ground shell powder to develop a new type of oil spill remediation agent with shell powder as a carrier. However, there are no reports on the use of calcined nano shell powder loaded with surfactants to stabilize foam and improve oil recovery. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method for preparing a nano shell powder foam stabilizer. The prepared nano shell powder foam stabilizer has good foam stabilizing performance, realizes the high-value development and utilization of shell powder resources, and is beneficial to environmental protection.

[0007] In order to solve the above technical problems, the technical solution of the present invention is:

[0008] A method for preparing a nano shell powder foam stabilizer comprises the following steps:

[0009] S1. Soak the shells in HCl solution for 24 hours, take them out and wash them with distilled water until they are neutral, and dry them to obtain pretreated shells;

[0010] S2. The pretreated shells obtained in step S1 are crushed and passed through a 150-mesh sieve to obtain coarse shell powder;

[0011] S3. The crude shell powder obtained in step S2 is placed in a tubular furnace, nitrogen is passed through, oxygen is isolated, the temperature is raised to 900-1000° C., and then calcined for 3-4 hours to obtain calcined shell powder;

[0012] S4. The calcined shell powder obtained in step S3 is ball-milled for 6-8h to obtain nano shell powder;

[0013] S5. Load the nano-shell powder, surfactant and deionized water obtained in step S4 into the lining of an autoclave, place the autoclave in an oven, heat it to 120°C and keep it warm for 24 hours, take out the lining after the autoclave cools to room temperature, pour out the mixed solution from the lining, filter the mixed solution and dry it to obtain the nano-shell powder foam stabilizer.

[0014] Furthermore, in step S1 of the present invention, the mass concentration of the HCl solution is 1%, the mass ratio of the shell to the HCl solution is 1:10, and the drying temperature is 60°C for 12 hours. The composition and structure of shellfish are similar, so the present invention is basically applicable to all shellfish including scallops and mussels.

[0015] Furthermore, in step S3 of the present invention, the flow rate of nitrogen is 100 mL / min.

[0016] Furthermore, in step S4 of the present invention, the rotation speed of the ball mill is 600-800 r / min, and the average particle size of the nano shell powder is 20-90 nm.

[0017] Furthermore, in step S5 of the present invention, the surfactant is sodium α-olefin sulfonate AOS, the ratio of the nano shell powder, surfactant and deionized water obtained in step S4 is 5g:1g:30mL; the drying temperature is 60°C and the drying time is 12h. AOS is an excellent surfactant commonly used in oil displacement and has good temperature and salt resistance.

[0018] The invention also provides a nano shell powder foam stabilizer prepared by the preparation method.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The microstructure of the nano shell powder obtained by the preparation method of the present invention changes, and its properties also change accordingly, and it has better stable foam performance. When the calcination temperature reaches above 900°C, the biological calcium carbonate in the shell powder component is converted into CaO, and the pH is increased from 7 to 9-10, which can play the role of alkali flooding and improve the recovery effect; and the CaO crystal form of the shell powder changes to form a large number of pore diameters, and the specific surface area increases, which helps to enhance the dispersion effect of the nano shell powder in water and the surfactant loading function, showing a good foam stabilization effect.

[0021] (2) The current shell powder-based cleaners and degreasers are mainly used in daily life and have a relatively relaxed use environment. The shell powder used has a large particle size and is compounded with a bio-surfactant. Such surfactants are easily biodegraded and are not suitable for high-temperature formation conditions. In comparison, the present invention takes into account the effect of particle size on the bottom layer, as well as the formation temperature and long-term effectiveness.

[0022] (3) Compared with other inorganic nano materials, the loose porous structure of the nano shell powder foam stabilizer prepared by the present invention makes it have a lower density, and the low-density particles can reduce the sedimentation of particles, which helps to form a stable foam structure. At the same time, the shell powder nanoparticles with a porous structure can adsorb more surfactants due to their internal and surface pores, reduce the adsorption loss of surfactants in the stratum, and help to form a stable foam structure in the oil reservoir. On the other hand, the amount of active calcium oxide generated can be controlled by controlling the calcination temperature and time. The active calcium oxide generated will generate calcium hydroxide when it meets water, and the solution is alkaline. The alkali can react with the petroleum acid in the crude oil to produce surfactants on the spot, reduce the oil-water interfacial tension, change the wettability of the rock surface, and promote the crude oil to form an emulsion, thereby further improving the oil recovery rate. In addition, the wettability of the nano shell powder can also be controlled by loading an excellent surfactant for oil displacement, to enhance its adsorption on the liquid film, thereby enhancing the stability of the foam and improving the oil displacement effect of the foam.

[0023] (4) The present invention realizes the high-value development and utilization of shell powder resources and is beneficial to environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of the present application, and do not constitute an improper limitation of the present invention. In the drawings:

[0025] Figure 1 This is a scanning electron microscope image of the nano-scallop shell powder foam stabilizer prepared in Example 1 of the present invention;

[0026] Figure 2 This is a particle size distribution diagram of a dispersion system formed by a nano-scallop shell powder foam stabilizer and water prepared in Example 1 of the present invention;

[0027] Figure 3 This is a particle size distribution diagram of the dispersion system formed by the unmodified nano scallop shell powder and water prepared in Comparative Example 1 of the present invention;

[0028] Figure 4 This is a scanning electron microscope image of the nano mussel shell powder foam stabilizer prepared in Example 2 of the present invention;

[0029] Figure 5 This is a particle size distribution diagram of a dispersion system formed by the nano mussel shell powder foam stabilizer and water prepared in Example 2 of the present invention;

[0030] Figure 6 This is a particle size distribution diagram of the dispersion system formed by the unmodified nano mussel shell powder and water prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0031] The present invention will be described in detail below in conjunction with specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0032] The instruments used in the specific implementation are as follows:

[0033] Tube furnace (BTH-GDY-SO3J); planetary ball mill (Pulverisette6); scanning electron microscope SEM (JSM-7610F); laser nanoparticle size (ZS90ZeTa); energy dispersive spectrometer EDS (NS7).

[0034] Example 1

[0035] Prepare the nano-scallop shell powder foam stabilizer according to the following steps:

[0036] S1. Soak the scallop shells in a 1% HCl solution at a mass ratio of 1:10 for 24 hours, wash them with distilled water until neutral, and dry them at 60°C for 12 hours to obtain pretreated scallop shells;

[0037] S2. The pretreated scallop shells obtained in step S1 are crushed and passed through a 150-mesh sieve to obtain coarse scallop shell powder;

[0038] S3. The crude scallop shell powder obtained in step S2 is placed in a tubular furnace, nitrogen is passed through at a flow rate of 100 mL / min, oxygen is isolated, the temperature is raised to 900° C., and then calcined for 3 h to obtain calcined scallop shell powder;

[0039] S4. The calcined scallop shell powder obtained in step S3 was ball-milled at a speed of 700 r / min for 6 h to obtain a nano-scallop shell powder with an average particle size of about 80 nm;

[0040] S5. Add the nano-scallop shell powder, sodium α-olefin sulfonate AOS and deionized water obtained in step S4 into the lining of the autoclave in a ratio of 5g:1g:30mL, place the autoclave in an oven, heat it to 120°C and keep it warm for 24h, take out the lining after the autoclave cools to room temperature, pour out the mixed solution from the lining, filter the mixed solution and dry it at 60°C for 12h to obtain the nano-scallop shell powder foam stabilizer. The morphological structure of the nano-scallop shell powder foam stabilizer was observed using a scanning electron microscope, and the results are as follows: Figure 1 As shown, the nano scallop shell powder foam stabilizer is a spherical particle.

[0041] The nano-scallop shell powder foam stabilizer obtained in step S5 was added into deionized water at a ratio of 1 g:100 mL, and after ultrasonic dispersion for 15 min, the foam stabilizer was stirred at a speed of 1000 r / min for 2 min using a high-speed stirrer to obtain a foam stabilizer A.

[0042] Comparative Example 1

[0043] The difference from Example 1 is that step S5 is not included, and the obtained product is unmodified nano scallop shell powder. The unmodified nano scallop shell powder foam stabilizer is added to deionized water at a ratio of 1 g:100 mL, and after ultrasonic dispersion for 15 min, the foam stabilizer is stirred at a speed of 1000 r / min for 2 min with a high-speed stirrer to obtain a foam stabilizer B.

[0044] Particle size testing

[0045] The particle size analysis of foam stabilizing solution A and foam stabilizing solution B was performed using a laser nanoparticle size analyzer. The test results are as follows: Figure 2 As shown, the particle size of the foam stabilizing solution A is mainly concentrated at 85nm, and the pH value is 10. Figure 3 As shown, the particle size of the foam stabilizing solution B is mainly concentrated at 190.7 nm, indicating that the modification step adopted in the present invention can effectively reduce the particle size.

[0046] Foam stability performance test

[0047] The conventional laboratory method Waring Blender method was used to determine the foamability and stability of the sample, and a 500md core was used for oil displacement experiments to determine the sample recovery. The samples were foam stabilizing solution A, foam stabilizing solution B, and AOS solution (AOS was added to deionized water at a ratio of 1g:100mL and stirred at a high-speed stirrer at 1000r / min for 2min). The test results are shown in Table 1:

[0048] Table 1

[0049] sample Foam volume (mL) Half-life(s) Recovery rate (%) Foam Stabilizing Solution A 685.9 689 65.8 Foam Stabilizing Solution B 552 605 58.7 AOS Solution 510 572 54.3

[0050] As shown in Table 1, the foam volume, half-life and recovery rate of the foam stabilizing solution A are better than those of the foam stabilizing solution B and the AOS solution, indicating that the modification step adopted in the present invention can improve the foam stabilizing performance.

[0051] Example 2

[0052] Prepare the nano mussel shell powder foam stabilizer by the following steps:

[0053] S1. Soak the mussel shells in a 1% HCl solution at a mass ratio of 1:10 for 24 hours, wash them with distilled water until they are neutral, and dry them at 60°C for 12 hours to obtain pretreated mussel shells;

[0054] S2. The pretreated mussel shells obtained in step S1 were crushed and passed through a 150-mesh sieve to obtain coarse mussel shell powder;

[0055] S3. The crude mussel shell powder obtained in step S2 is placed in a tube furnace, nitrogen is passed through at a flow rate of 100 mL / min, and then oxygen is isolated, the temperature is raised to 900° C. and calcined for 3 h to obtain calcined mussel shell powder;

[0056] S4. The calcined mussel shell powder obtained in step S3 was ball-milled at a speed of 700 r / min for 6 h to obtain nano mussel shell powder having an average particle size of about 70 nm;

[0057] S5. Add the nano mussel shell powder, sodium α-olefin sulfonate AOS and deionized water obtained in step S4 into the lining of the autoclave in a ratio of 5g:1g:30mL, place the autoclave in an oven, heat it to 120°C and keep it warm for 24h, take out the lining after the autoclave cools to room temperature, pour out the mixed solution from the lining, filter the mixed solution and dry it at 60°C for 12h to obtain the nano mussel shell powder foam stabilizer. The morphological structure of the nano mussel shell powder foam stabilizer was observed using a scanning electron microscope, and the results are as follows: Figure 4 As shown, the nano mussel shell powder foam stabilizer is a spherical particle.

[0058] The nano mussel shell powder foam stabilizer obtained in step S5 was added into deionized water at a ratio of 1 g:100 mL, and after ultrasonic dispersion for 15 min, the foam stabilizer was stirred at a speed of 1000 r / min for 2 min using a high-speed stirrer to obtain a foam stabilizer C.

[0059] Comparative Example 2

[0060] The difference from Example 2 is that step S5 is not included, and the obtained product is unmodified nano mussel shell powder. Unmodified nano mussel shell powder foam stabilizer is added into deionized water at a ratio of 1 g:100 mL, and after ultrasonic dispersion for 15 min, the foam stabilizer is stirred at 1000 r / min for 2 min with a high-speed stirrer to obtain foam stabilizer solution D.

[0061] Particle size testing

[0062] The particle size analysis of foam stabilizing solution C and foam stabilizing solution D was performed using a laser nanoparticle size analyzer. The test results are as follows: Figure 5 As shown in Figure 2, the particle size of the foam stabilizing solution C is mainly concentrated at 74 nm, and the Ph value is 9.3. Figure 6 As shown, the particle size of the foam stabilizing solution D is mainly concentrated at 204.7 nm, indicating that the modification step adopted in the present invention can effectively reduce the particle size.

[0063] Foam stability performance test

[0064] The conventional laboratory method Waring Blender method was used to determine the foaming and stability of the samples. The recovery rate of the samples was measured using a 500 md core for oil displacement experiments. The samples were foam stabilizing solution C, foam stabilizing solution D, and AOS solution (AOS was added to deionized water at a ratio of 1 g:100 mL and stirred at a high-speed stirrer at 1000 r / min for 2 min). The test results are shown in Table 2:

[0065] Table 2

[0066] sample Foam volume (mL) Half-life(s) Recovery rate (%) Foam Stabilizing Solution C 655.2 701 67.1 Foam Stabilizing Solution D 519 627 59.4 AOS Solution 510 572 54.3

[0067] As shown in Table 2, the foam volume, half-life and recovery rate of the foam stabilizing solution C are better than those of the foam stabilizing solution D and the AOS solution, indicating that the modification step adopted in the present invention can improve the foam stabilizing performance.

[0068] Example 3

[0069] Prepare the nano-scallop shell powder foam stabilizer according to the following steps:

[0070] S1. Soak the scallop shells in a 1% HCl solution at a mass ratio of 1:10 for 24 hours, wash them with distilled water until neutral, and dry them at 60°C for 12 hours to obtain pretreated scallop shells;

[0071] S2. The pretreated scallop shells obtained in step S1 are crushed and passed through a 150-mesh sieve to obtain coarse scallop shell powder;

[0072] S3. The crude scallop shell powder obtained in step S2 is placed in a tubular furnace, nitrogen is passed through at a flow rate of 100 mL / min, oxygen is isolated, the temperature is raised to 950° C., and calcined for 3.5 h to obtain calcined scallop shell powder;

[0073] S4. The calcined scallop shell powder obtained in step S3 was ball-milled at a speed of 600 r / min for 6.5 h to obtain a nano-scallop shell powder with an average particle size of about 90 nm;

[0074] S5. The nano scallop shell powder, sodium α-olefin sulfonate AOS and deionized water obtained in step S4 are loaded into the lining of the autoclave in a ratio of 5g:1g:30mL, the autoclave is placed in an oven, the temperature is raised to 120°C and then kept warm for 24h, the lining is taken out after the autoclave cools to room temperature, the mixed solution is poured out from the lining, the mixed solution is filtered and dried at 60°C for 12h to obtain the nano scallop shell powder foam stabilizer.

[0075] Example 4

[0076] Prepare the nano mussel shell powder foam stabilizer by the following steps:

[0077] S1. Soak the mussel shells in a 1% HCl solution at a mass ratio of 1:10 for 24 hours, wash them with distilled water until they are neutral, and dry them at 60°C for 12 hours to obtain pretreated mussel shells;

[0078] S2. The pretreated mussel shells obtained in step S1 were crushed and passed through a 150-mesh sieve to obtain coarse mussel shell powder;

[0079] S3. The crude mussel shell powder obtained in step S2 is placed in a tube furnace, nitrogen is passed through at a flow rate of 100 mL / min, and then oxygen is isolated, the temperature is raised to 1000° C., and then calcined for 4 h to obtain calcined mussel shell powder;

[0080] S4. The calcined mussel shell powder obtained in step S3 was ball-milled at a speed of 800 r / min for 8 h to obtain nano mussel shell powder having an average particle size of about 20 nm;

[0081] S5. The nano mussel shell powder, sodium α-olefin sulfonate AOS and deionized water obtained in step S4 are loaded into the lining of an autoclave in a ratio of 5g:1g:30mL, the autoclave is placed in an oven, the temperature is raised to 120°C and then kept warm for 24h, the lining is taken out after the autoclave cools to room temperature, the mixed solution is poured out from the lining, the mixed solution is filtered and dried at 60°C for 12h to obtain a nano mussel shell powder foam stabilizer.

[0082] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a nano shell powder foam stabilizer, characterized in that: The following steps are involved: S1. Soak the shells in HCl solution for 24 hours, take them out and wash them with distilled water until they are neutral, and dry them to obtain pretreated shells; S2. The pretreated shells obtained in step S1 are crushed and passed through a 150-mesh sieve to obtain coarse shell powder; S3. The crude shell powder obtained in step S2 is placed in a tubular furnace, nitrogen is passed through, oxygen is isolated, the temperature is raised to 900-1000° C., and then calcined for 3-4 hours to obtain calcined shell powder; S4. The calcined shell powder obtained in step S3 is ball-milled for 6-8h to obtain nano shell powder; S5. Load the nano-shell powder, surfactant and deionized water obtained in step S4 into the lining of an autoclave, place the autoclave in an oven, heat it to 120°C and keep it warm for 24 hours, take out the lining after the autoclave cools to room temperature, pour out the mixed solution from the lining, filter the mixed solution and dry it to obtain the nano-shell powder foam stabilizer.

2. The method for preparing a nano shell powder foam stabilizer according to claim 1, wherein: In the step S1, the mass concentration of the HCl solution is 1%, and the mass ratio of shells to the HCl solution is 1:10; the drying temperature is 60° C. and the drying time is 12 h.

3. The method for preparing a nano shell powder foam stabilizer according to claim 1, wherein: In step S3, the flow rate of nitrogen is 100 mL / min.

4. The method for preparing a nano shell powder foam stabilizer according to claim 1, wherein: In step S4, the rotation speed of the ball mill is 600-800 r / min, and the average particle size of the nano shell powder is 20-90 nm.

5. The method for preparing a nano shell powder foam stabilizer according to claim 1, wherein: In the step S5, the surfactant is sodium α-olefin sulfonate AOS, and the ratio of the nano shell powder, surfactant and deionized water obtained in step S4 is 5g:1g:30mL; the drying temperature is 60°C and the drying time is 12h.

6. A nano shell powder foam stabilizer obtained according to the preparation method described in any one of claims 1 to 5.

Citation Information

Cited By

  • A foam stabilizer based on graded modification of enteromorpha and a preparation method and application thereof

    CN121343578B

  • Salt-tolerant CO2 foam oil displacement system, preparation method and application method

    CN122381790A

  • A salt-tolerant CO2 foam flooding system, its preparation method and application method

    CN122381790B